Lecciones aprendidas en la implementación del Manejo Integrado Costero: las experiencias demostrativas del ecosistema Sabana- Camagüey, Cuba. - Alcolado, P. M. (Universidad de El Salvador, 2016)
In the Sabana-Camagüey archipelago, Cuba, and its coastal marine areas, advances in the implementation of Integrated Coastal Management have been achieved through the establishment of Demonstrative Programs among other actions. For that, the execution of the “Sabana-Camagüey Ecosystem” UNDP/GEF Project during 20 years was decisive. Outstanding outcomes, applied strategies and actions,  lessons learned, and their importance for protecting and sustainably use of biodiversity and for facing threats of both climate change and variability are described herein. Key actions were: (1) an intense and systematic stakeholder education, awareness and capacity building to key stakeholders about issues related to ICM and biodiversity since the beginning of the Project, at the involved national, province and municipality levels; as well as (3) a strong participation of key stakeholders (government, productive sectors, scientific and teaching institutions, communities, and non-governmental organizations). The governance process was based on the ECOCOSTAS/Coastal Resource Center-University of Rhode Island conception and methodology, including the application of the known MIC generation cycle, the four result orders, and the support from science and the best available knowledge. Recent results are provided about the application, by the UNDP/GEF Sabana-Camagüey Ecosystem Project, of an annual ICM operative performance self-assessment form. This was carried out in a participative way in seven ICM  demonstrative Programs for the Sabana-Camagüey Ecosystem, which intervention areas were declared and certified as “Zones under Integrated Coastal Management Regime”. Each ICM program was led by the local government and had it particular composition and integration structure.